Support Needs of Expectant Mothers and Fathers: A Qualitative Study - Widarsson, Margareta (Springer Publishing Company, 2012)
The aim of this study was to describe expectant mothers’ and fathers’ perceived needs of support during pregnancy. Twenty-two women and 10 men were interviewed in four focus groups and 13 individual interviews. Systematic text condensation was performed to analyze the data. Parents described not only a broad spectrum of social support needs but also needs of psychological and physical support. They also requested to share their experiences with others. The foci of care and parents’ needs of support are more harmonized with medical support than with psychological and emotional support. Mothers’ needs were predominately addressed in the health services, but fathers often felt “invisible.” Antenatal services may need to offer more customized individual support and emphasize peer support in groups; the challenge is to involve both parents through communication and encouragement so they can support each other.